The Palestinian Vernacular Dialect: A Perpetual Heritage - Amani AL-JUNAIDI (Turath, 2024)
The classical Arabic language has preserved pronunciations, vocabulary, and meanings, such that it has closely linked the Arabs from East to West linguistically. However, the cultural linguistic sound of the pronunciation of the Arabic letters among all Arabs is variable, for each of these countries has such a way that it forms the identity of the person linked to his place, and since the Palestinian dialect is one of the dialects of the Levant, but it has a specificity that differs from other Levantine dialects, even if they are similar. I must point out the importance of the sense of hearing in perceiving linguistic sound and the way it is pronounced, and that learning colloquial dialects is by word of mouth. However, there are some clear details that can be monitored by scientific research to clarify the aesthetics of dialects in general.